THE COOPERATIVE LEARNING: THREE-STEP INTERVIEWTOWARDS STUDENTS' SPEAKING ABILITY - Rio Nur Iman, - (2009)
The purpose of this study is to investigate the implementation of Cooperative Learning: Three-Step Interview towards student's speaking ability. In addition, the study also tries to find out the student's response of the technique. This study used experimental method. The respondents were SMAN 4 Bandung students. Two classes were taken as samples of the total respondents. The study used a set of instrument. Pretest and posttest were conducted to measure the student's speaking ability. In addition, questionnaire and interview were given to obtain further information about the technique. The result shows that there is a significant difference between the progresses of both groups. The progress of experimental group is greater than the control group. It reveals that Cooperative Learning: Three-Step Interview is effective to improve student's speaking ability. In addition to the result above, based on the questionnaire and interview, most of respondents responded positively to the technique. They stated that the learning was meaningful and fun. Furthermore, their speaking progress improved after learning through the technique.